Carbon benefits through agroforestry transitions on unmanaged fallow agricultural land in Hawaiʻi - Leah L. Bremer; Gina McGuire; Zoe Hastings Silao; Natalie Kurashima; Tamara Ticktin; Susan E. Crow; Christian P. Giardina; Kawika B. Winter; Nathan DeMaagd; Clay Trauernicht (Scientific Reports)
Abstract There are growing efforts to incorporate agroforestry into ecosystem service incentive programs. Indigenous and other place-based multi-strata agroforestry systems are important conservation and agricultural strategies, yet their ecosystem services, including carbon sequestration benefits, have received little research attention. To fill this gap, we draw on interviews with agroforestry practitioners and ecosystem service modeling in Hawaiʻi to: (1) create future scenarios of where fallow unmanaged agricultural and non-native dominated conservation lands could be transitioned to multi-strata agroforestry under current and future climates; and (2) quantify the potential above-ground carbon and soil carbon benefits and tradeoffs of transitions across these scenarios. We found that about half of unmanaged fallow agricultural lands, representing >1,500 km2 , was suitable for agroforestry transitions under current rainfall and over a third, representing >1,200  km2, remained suitable under a dry climate change scenario, RCP 8.5 mid-century. Mean above-ground carbon in modeled agroforestry systems was estimated to be 92–125 Mg C ha-1 (337–458 Mg CO2 ha-1) with ~75%  of the potential restoration area projected to significantly increase above-ground carbon storage. Considering both above-ground and soil carbon, overall carbon benefits are expected across over a third of the potential restoration area with just 5% of the area with expected overall losses. These results provide evidence for potential carbon hotspots for agroforestry transitions, as well as to the need for further study of soil carbon changes with multi-strata agroforestry transitions across varying climates and soil types. With potential carbon sequestration similar to or greater than that of native forest restoration, restoration through agroforestry represents an important pathway to achieving carbon benefits through multi-benefit forest-agricultural systems on large areas of unmanaged agricultural lands, offering a pathway to support inclusive and effective natural climate solutions.